2022
DOI: 10.3389/fonc.2022.945820
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in laryngeal cancer: What should we expect from a meta-analysis?

Abstract: BackgroundAlthough many studies have shown the predictive value of the high neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) for various cancers, there are conflicting reports regarding their role in laryngeal cancer. This study aimed to evaluate the relationship between high NLR/PLR and laryngeal cancer prognosis with the help of meta-analysis.MethodsPubMed, Embase and other databases were used to search relevant studies. The pooled hazard ratio (HR) and 95% confidence interval (CI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…To the best of our knowledge, this is the first meta‐analysis to explore the prognostic value between pretreatment NLR and hypopharyngeal cancer. In a previous study 23 that included 5716 patients from 20 studies, high NLR was shown to be associated with poor OS, PFS, and DFS in laryngeal cancer. Takenaka et al, 24 Tham et al, 25 and Takenaka et al's 26 high‐quality studies also demonstrated the relationship between NLR and head and neck cancer, confirming that high pretreatment NLR is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first meta‐analysis to explore the prognostic value between pretreatment NLR and hypopharyngeal cancer. In a previous study 23 that included 5716 patients from 20 studies, high NLR was shown to be associated with poor OS, PFS, and DFS in laryngeal cancer. Takenaka et al, 24 Tham et al, 25 and Takenaka et al's 26 high‐quality studies also demonstrated the relationship between NLR and head and neck cancer, confirming that high pretreatment NLR is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years many retrospective studies have been conducted to determine the value of systemic inflammatory parameters as potential prognostic biomarkers in HNSCC, [13][14][15] including LSCC. 7,[16][17][18][19][20] However, most of these studies were designed and performed on heterogeneous series of patients, comprising different tumor locations and treatment regimens. For this reason, this work was focused on a specific location (the glottis) and stages (early stages I and II), as well as a single treatment (TLS) to assess the prognostic relevance of preoperative hematological parameters specifically in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are no validated biomarkers to guide the clinical management and decision making for LSCC patients. In recent years many retrospective studies have been conducted to determine the value of systemic inflammatory parameters as potential prognostic biomarkers in HNSCC, 13–15 including LSCC 7,16–20 . However, most of these studies were designed and performed on heterogeneous series of patients, comprising different tumor locations and treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations